Soil microbiology - Tate, Robert L. (Wiley, 1995)
This introduction to soil\environmental microbiology has been designed to provide an understanding of the diversity of life contained within a gram of soil as well as the intricacies of the linkages of these living entities with terrestrial life in general. Topics are presented and analyzed with an emphasis on modern environmental concerns. Many of the principles are exemplified with data relating to food production, but the majority are demonstrated through an analysis of currently pressing environmental problems.